Commentary: How and Why Does Poetry Matter? And What Do We Do About That? (LEARNing Landscapes, 2010)
While there is a long and widely held belief that poetry matters and is a necessary component of the school curriculum, such convictions are at odds with the way poetry is taught and the general antipathy that students, especially in secondary school, hold towards it. Such disregard is well established among most school teachers who have been similarly schooled and consequently distrust their own competence as readers of poetry and unwittingly perpetuate such insecurity. Teachers need to act with some urgency to determine why poetry is such a valuable cultural and social good, and consider the easily accessible means by which poetry can be enthusiastically embraced by their pupils.
Keywords: poetry; curriculum; culture; secondary school; student